Scattering mechanisms of electrons in monocrystalline PbTe, PbSe and PbS - Freik, D.M.; Nykyruy, L.I.; Shperun, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The theoretical analysis of carrier scattering mechanisms in electronic lead chalcogenide crystals was carried out. The calculation of carrier mobility in wide temperature (4.2-300 К) and concentration (10¹⁶-10²⁰ сm⁻³) ranges is carried out from the viewpoint of interaction of conductivity electrons with deformation potentials of acoustic and optical phonons, polarizing potential of optical phonons, screening Coulombic and short-range potentials of vacancies. It has been shown that the agreement of theoretical and experimental results takes place when taking into account the carrier scattering both on phonons and ionized vacancies.